A study on auditory perception of tense and lax vowels of English as a FL by learners with Spanish as L1 - Bustos, Jose; Vignolo, Francisca; Vyhmeister, Gerald (Teaching English as a Foreign Language Journal, 2023)
Different studies in the field of perception of second-language sounds (L2) suggest that English learners with Spanish as their mother tongue language (L1) are influenced by the sounds of their L1 to perceive the sounds in the L2. As a result, learners are not able to perceive speech sounds as they are in English, because they assimilate the sounds of the foreign language (FL) based on their L1 (Best & Tyler, 2007; Gibson & Gibson, 1955). The objective of this research is to explore the capacity of perception of tense and lax vowels of English (Standard British accent) in 8 high school students from two subsidised schools in Chillán and San Carlos, Chile. The age of the participants range from 15 to 18 years old. One auditory perception test was used: An Identification Test was applied to measure the capacity of the participants to perceive lax and tense vowels: /i:/, /ɪ/, /æ/ and /^/.